IMPACT OF 5S ON BUSINESS PERFORMANCE THROUGH LEAN MANAGEMENT AND BLUE OCEAN LADERSHIP IN THE INDONESIAN MANUFACTURING INDUSTRY - Maemunah, Siti; Rayyan, Rayyan (Jurnal Riset Bisnis dan Manajemen, 2025)
Business competition in the manufacturing sector is increasingly high and unpredictable. Tight investment in capital and human resources requires companies to ensure 5S practices, the basic concepts of Japanese culture and lean management need to be applied to improve business performance in Indonesia, especially at PT. Manufacturing. This research uses a PLS-SEM approach. A total of 85 respondents were in division head positions. The research results show that 5S has no direct or indirect influence on business performance. The results show that lean management and blue ocean leadership do not have a mediating effect between 5S and business performance. Blue ocean leadership has not been implemented optimally by the leadership, so performance has not met expectations. Contribution of researchers to PT. Manufacturing helps top management in companies implement and execute 5S well in the company. The second contribution concerns the need to improve lean management in the pull system.